Evaluation of the cytotoxic effect of Salvia triloba on Osteosarcoma (U2OS) cell line - Abd El-bary, Rowan Bahaa El-din (AUC Knowledge Fountain, 2020)
Despite the huge advancement in the field of cancer treatment, the conventionally used treatments still present significant challenges such as low effectiveness and adverse side effects. Thus, there is a critical need to continuously develop new, more effective and safe drugs against cancer. Herbal plants serve as a potential source for a wide variety of complex compounds with probable anticancer activity. The genus Salvia encompasses about 900 species. Salvia triloba, commonly known as Greek sage, is native to the Middle East and is inherently linked to local traditional medicine systems. It was recently shown to possess anti-proliferative activity against breast cancer cell lines. However, there is no experimental evidence regarding the anticancer effects of Salvia triloba on osteosarcoma. In this study, we investigated the effect of Salvia triloba ethanol and acetone extracts, as well as the thin-layer chromatography-fractionated acetone extract on viability, and the effect of both crude extracts on the migratory ability of U2OS osteosarcoma cells. MTT results have shown that the acetone crude extract exhibits the most potent cytotoxic effect, indicating the positive cooperative interactions between the different compounds present in the plant material. Moreover, trans-well migration assay illustrated that acetone crude extract was more powerful than the ethanol extract in hindering cellular migration. Furthermore, we show that Salvia triloba has no significant hemolytic activity and most likely will target anionic cancer cells while sparing the healthy neutral cells (erythrocytes). In conclusion, our results have shown that Salvia triloba inhibits U2OS cells’ proliferation, migration and showed no considerable hemolytic activity on human erythrocytes upon application. Altogether, these results promote the novel therapeutic potential of Salvia triloba as an anticancer drug.